Food sovereignty, food security, and international trade: evidence from Chile - Silva, Andres; Barrera, Arturo; Ribera, Luis; del Valle, Martin (Frontiers in Sustainable Food Systems, 2024)
There is an ongoing debate regarding the role of international trade on food security and food sovereignty. While food security is a concept with a recognized definition and methodologies to assess it, food sovereignty has multiple definitions, and it is not clear how to measure it. Our purpose is to analyze the evolution of cherry and avocado domestic purchases as an illustrative example of the role of international trade on food security and food sovereignty. Using a descriptive analysis, we found that cherry and avocado exports have increased over the last decades. We found that domestic cherry and avocado purchases have been stable, while the overall fruit and vegetable purchases have been decreasing. Besides, the cherry seasons are showing some signs of expansion. In terms of disparities, households from quintiles 1 and 2, the two lowest income quintiles, increased cherry purchases. Moreover, households from quintiles 4 and 5, the two highest income quintiles, decreased cherry purchases. International trade can also help to increase domestic purchases and decrease purchases disparities, which can be linked to food access and food security. However, the increased of off-season imports of avocado can be linked to a decreased food sovereignty. We expect to contribute to illustrate how international trade, food security and food sovereignty are linked, while the concept of food sovereignty keeps developing.